2012
DOI: 10.1021/la301938f
|View full text |Cite
|
Sign up to set email alerts
|

Interactions and Binding Energies of Dimethyl Methylphosphonate and Dimethyl Chlorophosphate with Amorphous Silica

Abstract: The fundamental interactions of dimethyl methylphosphonate (DMMP) and dimethyl chlorophosphate (DMCP) on amorphous silica nanoparticles have been investigated with transmission infrared spectroscopy and temperature-programmed desorption (TPD). DMMP and DMCP both adsorb molecularly to silica through the formation of hydrogen bonds between isolated silanols and the phosphoryl oxygen of the adsorbate. The magnitude of the shift of the ν(OH) mode upon simulant adsorption is correlated to the adsorption strength. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(85 citation statements)
references
References 23 publications
14
71
0
Order By: Relevance
“…Simultaneously, most of the signals related to NO 3 − and OH − groups disappeared. These new bands correspond to the vibration modes of adsorbed DMCP . The most intense band located at 1053 cm −1 is not related to DMCP and it is linked to vibrations of Cu 2 (PO) 4 .…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Simultaneously, most of the signals related to NO 3 − and OH − groups disappeared. These new bands correspond to the vibration modes of adsorbed DMCP . The most intense band located at 1053 cm −1 is not related to DMCP and it is linked to vibrations of Cu 2 (PO) 4 .…”
Section: Resultsmentioning
confidence: 90%
“…After 14 h, a band at 1186 cm −1 becomes visible. This band is attributed to ρ (CH 3 O) of the DMCP molecule . After 44 h, a small shoulder band at 1062 cm −1 appears, which is linked either to the symmetric stretching of CO or to the antisymmetric vibration mode of the phosphate–copper complexes .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the year 2012, Wilmsmeyer et al, showed that common stimulant, an organophosphorus compound, namely DMMP (dimethyl methylphophonate) binded hydrophilic silica more significantly than DMCP (dimethyl chlorophosphate), indicating that the sarin phosphorus‐halogen bond affects the surface chemistry of the agent in a complicated way . Then in the year 2014, Davis et al studied the energetics and mechanisms that regulated the hydrogen‐bonding interactions when soman and sarin adsorb on silica .…”
Section: Applications Of Msnsmentioning
confidence: 99%
“…The adsorption and decomposition of gaseous DMMP molecules on various metal oxides, such as SiO 2 , Al 2 O 3 , MgO, La 2 O 3 , and Fe 2 O 3 , have been investigated by numerous research groups [4,[8][9][10][11][12][13]. Besides, the mixed structure of different metal oxides (or supported metal oxides) and nano-sized metal oxides have been also examined for the decontamination of DMMP molecules [14][15][16][17][18][19], and, recently, the utilization of photo-catalysts has been also suggested [20,21].…”
Section: Introductionmentioning
confidence: 99%